Bias awareness in teachers: a German adaptation of the bias awareness scale for teachers - Fehringer, Benedict C.O.F.; Bonefeld, Meike; Schunk, Fabian (Social psychology of education, 2025)
Bias Awareness is understood as individual differences in people’s sensitivity to and concerns about their expressions of subtle bias. In 2015, Perry et al. developed a scale to measure the awareness and concern of one’s own subtle bias (Bias Awareness Scale, BAS). The present research aims to test the validity of a German adaptation of the Bias Awareness Scale especially for teachers. To this end, different aspects of evidence of validity were analyzed. The complete sample consists of N = 241 participants from four subsamples, each focusing on different related constructs of bias awareness. The study supported the validity of the German version of the BAS as a measurement of subtle bias against people with migration background. In addition to content validity, the results demonstrated convergent and discriminant validity regarding prejudiced thought and behavior as well as delivered evidence for a single factor structure of the scale. Furthermore, the study also showed a difference in gender with a higher bias awareness for females.